Kinematic analysis of figure skating jump by using wearable inertial measurement units - Shi, Y.; Ozaki, A.; Honda, M. (Proceedings, 2020)
The purpose of this study was to demonstrate the feasibility of measuring and analyzing characteristics of figure skating jumps using wearable sensors. One elite figure skater, outfitted with five inertial measurement units (IMUs), performed flip jumps with single, double, and triple revolutions. Take-off event and flight phase of each trial were under analysis. Kinematic differences among jumps with variant revolutions as well as key factors for performing successfully landed triple jumps were determined by IMU signals. Compared with a video-based method, this study revealed the following characteristics that coincide with previous studies: at take-off event, the skater performed pre-rotation and took off with preferred postural positions as revolutions increased (p < 0.01); during flight, the skater struggled more to maintain the smallest inertial of moment as revolutions increased (p < 0.01); in order to perform successfully landed jumps, it was crucial that the skater improved the control of preparation for flight at take-off (p < 0.05).